An Analysis of Students’ Difficulties in English Conversation Practice - Joko Prayudha.S; Ami Pradana (Journal Corner of Education, Linguistics, and Literature, 2023)
Speaking skill is the most important language skills to support communication, especially in English speaking skills are needed for two-way communication that can be understood by one another. However, there are still many students who are not maximal in carrying out English conversations practice to improving their English speaking skills. Therefore, this study aims to analyze students' problems and difficulties in practicing English conversation in order to improve speaking skills. The method used in this research is qualitative by using a descriptive approach. Data were obtained through direct observation and interviews related to the conditions experienced by students in improving their English speaking skills. After the data has been obtained, the data is analyzed through three stages, namely data reduction, data display and data conclusion. The results showed that students had difficulty practicing English conversations due to a lack of confidence, lack of courage, fear of being wrong, not having enough English vocabulary and not having a supportive environment to practice English conversations. Therefore, it is necessary to have a good learning strategy to encourage students to be able to practice speaking in English.